2020
DOI: 10.3390/jfmk5020041
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short-Term High-Intensity Interval Training and Moderate Intensity Continuous Training on Body Fat Percentage, Abdominal Circumference, BMI and VO2max in Overweight Subjects

Abstract: We aimed to compare the effects of a personalized short-term high-intensity interval training (HIIT) vs. standard moderate intensity continuous training (MICT) on body fat percentage, abdominal circumference, BMI and maximal oxygen uptake (VO2max) in overweight volunteers. Twenty overweight sedentary volunteers (24.9 ± 2.9y; BMI: 26.1 ± 1 kgm−2) were randomly assigned to 2 groups, HIIT or MICT. HIIT trained 6 weeks (3-days/week), 40-min sessions as follows: 6-min warm-up, 20-min resistance training (RT) at 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Ram et al, 2020. However previous studies concluded that HIIT has big effect in fat oxidation and losing weight (Russomando et al, 2020). Russomando and his colleagues results that HIIT has positive trends in the reduction of fat mass percentage.…”
Section: Introductionmentioning
confidence: 95%
“…Ram et al, 2020. However previous studies concluded that HIIT has big effect in fat oxidation and losing weight (Russomando et al, 2020). Russomando and his colleagues results that HIIT has positive trends in the reduction of fat mass percentage.…”
Section: Introductionmentioning
confidence: 95%
“…Penelitian menunjukkan bahwa efek dari latihan interval intensitas tinggi mungkin lebih terlihat setelah periode latihan yang lebih panjang. Hal ini sejalan dengan temuan penelitian ini, di mana efek dari latihan kombinasi HIIT dan MICT mungkin memerlukan waktu yang lebih lama untuk terlihat dalam perubahan berat badan dan lemak tubuh (Russomando et al, 2020;Sarifudin et al, 2023;Wang & Zhang, 2023;Warthadi et al, 2022).…”
Section: Pembahasanunclassified
“…Even a single bout of HIIT (4 × 30s "all out" sprints with ~4-mins recovery) as Whyte, et al showed, improved glucose tolerance, insulin sensitivity and fat oxidation in obese men [13]. Other studies conducted with overweight and obese individuals haveused a modified HIIT protocol for 2-6-weeks, which is likely to be more practical for overweight and obese populations than Wingate and reported improvements in body composition, insulin sensitivity, lipid profile and VO2max [14][15][16][17].…”
Section: Participantsmentioning
confidence: 99%